The Mckittrick-Wheelock Syndrome: A Rare Cause of Severe Hydroelectrolyte Disorders and Acute Renal Failure - Andrea Bruno; Domenico Chimienti; Alda Montanaro; Fernando Prete; Pasquale Libutti; Piero Lisi; Carlo Basile (Case Reports in Nephrology)
The McKittrick-Wheelock syndrome is a rare cause of severe hydroelectrolyte disorders and fluid depletion as a result of rectal tumor hypersecretion, which can lead to acute renal failure. We report the case of a 70-year-old female who presented with hyponatremia, hypokalemia, hypochloremia, and acute renal failure, due to a watery, mucinous diarrhea. A large rectal villous adenoma was discovered on ileocolonoscopy, and definitive management was achieved by removal of the tumor. In conclusion, reversal of the biochemical derangement is the cornerstone of successful management of the McKittrick-Wheelock syndrome. Then, immediate surgical resection of the tumor is the treatment of choice.